Achieving excellence: Mastering mindset for peak performance in sport and life - Hacker, C. M.; Mann, M. E. (Human Kinetics, 2022)
Perform to your potential with proven mental training techniques! Achieving Excellence: Mastering the Mindset for Peak Performance in Sport and Life offers a variety of peak performance strategies to help athletes, coaches, and performers of all kinds achieve a winning mindset. The book explores sport psychology concepts and provides practical, proven strategies to incorporate into your daily life and competitive career.